The Numerical and Approximate Analytical Solution of Parabolic Partial Differential Equations with Nonlocal Boundary Conditions - Ghoreishi, Seyed Mohammad (2011)
Many scientific and engineering problems can be modeled by parabolic partial differential equations with nonlocal boundary conditions. Examples of such problems can be found in chemical diffusion, thermoelasticity, heat conduction processes, nuclear reactor dynamics, inverse problems, control theory and so forth. In the last two decades, the development of numerical and approximate analytical techniques to solve these equations has been an important area of research due to the need to better understand the underlying physical phenomena.